Enhancement of biological treatment by using moving bed biofilm reactor (MBBR) for rubber glove wastewater: article - Tengku Kamarulzaman, Tengku Darwina Irfani; Lim, Ying Pei (2019)
Operational parameters and effluent properties are the most important factors affecting the successful rate of biological treatment in wastewater treatment process. The main objective of this study was to access the feasibility of using moving bed biofilm reactor (MBBR) to enhance biological treatment of effluent from rubber glove manufacturing process. The effect of three operational parameters i.e hydraulic retention time (HRT), organic loading rate (OLR) and percent filling towards removal of chemical oxygen demand (COD) was studied. The rubber glove wastewater contains high organic loads and suspended solids that exceed the permissible limits set by the authority. Control test shows that the presence of biomedia increased COD removal. In addition, the higher the percent filling of biomedia in the wastewater, the higher the COD removal as the HRT prolong. The optimum HRT for MBBR is 8 hour with 62.4% of COD removal. The result also shows no trend of increasing organic loading rate with COD removal rate. However, COD removal increased with HRT regardless of the organic loading rate. In conclusion, MBBR shows promising alternative to enhance COD removal in comparison with conventional biological process in rubber glove wastewater treatment.